(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the use of visual supports, such as images and videos, in enhancing listening comprehension. It highlights the benefits of visual aids, including providing contextual information, supporting memory retention, reducing cognitive load, and engaging various learning styles. The article discusses different types of visual supports—images, infographics, videos, and interactive visuals—and provides practical strategies for incorporating these tools into listening activities, such as pre-listening, while-listening, and post-listening exercises. The conclusion emphasizes the effectiveness of visual supports in creating an engaging and inclusive learning environment, and the potential for future innovations in using multimedia to improve listening skills. Key words: Listening comprehension, visual supports, images, videos, learning styles, cognitive load, memory retention, educational technology, interactive visuals, language learning, auditory processing, infographics, multimedia learning